2020
DOI: 10.48550/arxiv.2008.09908
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Black Hole Shadows in M-theory Scenarios

A. Belhaj,
M. Benali,
A. El Balali
et al.

Abstract: We study the shadows of four dimensional black holes in M-theory inspired models. We first inspect the influence of M2-branes on such optical aspects for non-rotating solutions. In particular, we show that the M2-brane number can control the circular shadow size. This geometrical behavior is distorted for rotating solutions exhibiting cardioid shapes in certain moduli space regions. Implementing a rotation parameter, we analyze the geometrical shadow deformations. Among others, we recover the circular behavior… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 25 publications
4
14
0
1
Order By: Relevance
“…Parallelly to these efforts, optical behaviors have been investigated by considering the deflection angle of lights and the shadow geometry [10][11][12][13][14][15][16]. Concretely, the black hole shadow behaviors have been examined in different theories including M-theory and superstring theory in the presence of D-brane objects [17,18]. The visualization of the shadow cast using the null geodesic equations has been completed by the study of geometrical observables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallelly to these efforts, optical behaviors have been investigated by considering the deflection angle of lights and the shadow geometry [10][11][12][13][14][15][16]. Concretely, the black hole shadow behaviors have been examined in different theories including M-theory and superstring theory in the presence of D-brane objects [17,18]. The visualization of the shadow cast using the null geodesic equations has been completed by the study of geometrical observables.…”
Section: Introductionmentioning
confidence: 99%
“…For non-rotating black holes, it has been revealed that the shadow has a circular geometry where its size can be controlled by the mass and other parameters including the charge and dark energy [19]. This geometric manifestation is distorted for ordinary rotating black holes, to exhibit either the D-shape or the cardioid geometries [17,18,20,21]. In addition, it has been shown that the shadow behaviors depend also on other parameters including the brane number and a cosmological scale [18,22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been observed that the shadow aspects could depend also on geometric and stringy parameters. Indeed, the brane number and cosmological scale have been implemented where non-trivial geometries have been appeared [34,35]. In this work, we aim to investigate the optical behaviors of Bardeen AdS black holes by examining the corresponding shadows using one dimensional real curves.…”
Section: Introductionmentioning
confidence: 99%
“…The circular geometric manifestation can be distorted by introducing the rotating parameter which generates nontrivial geometries involving either D or cardioid shapes [14,15,[17][18][19][20]. The latter has been appeared in the study of AdS black holes obtained from type superstrings and Mtheory scenarios using brane physics [19,21]. Certain distorted geometrical behaviors have been observed for rotating stringy solutions exhibiting cardioid shapes by varying the brane number.…”
Section: Introductionmentioning
confidence: 99%